Effect of Nb on nanoquasicrystalline Al-based alloys - Galano, M; Audebert, F; Stoney, I; Cantor, B (2008)
Nanoquasicrystalline Al-based alloys, containing icosahedral particles in an -Al matrix, exhibit high strength at elevated temperature. The metastability of the quasicrystals can limit the use of these alloys. In the present work, the microstructural evolution of Al93(Fe3Cr2)7 and Al93Fe3Cr2Nb2 (at%) alloys was studied using heat treatments and structural characterization by XRD, TEM and STEM-EDX analysis. It was observed that the Nb is dissolved in the Al-Fe-Cr icosahedral phase. This provides higher thermal stability, retaining the fine nanoquasicrystalline microstructure for longer times at high temperature.